Critical analysis of environmental impact assessment as a prerequisite for developmental projects in South Africa - Kalembo, Marble Bore (My University, 2021)
An Environmental Impact Assessment (EIA) is an environmental tool used to assess possible and expected adverse impact that might occur as a result of a proposed developmental project, in a vulnerable area and environment. All project developments must be socially, environmentally and economically sustainable. For any such projects to be sustainable, Environmental Impact Assessment must be conducted as a prerequisite for the development of the projects. This must be done in compliance with environmental legislation, to ensure that proposed developments benefit current and future generations, while at the same time protecting the environment. Environmental degradation must be minimized, where possible prevented for environmental protection, and sustainability
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2021
Keywords: Environmental impact assessment; Development projects; South Africa; Environmental impact analysis; Economic development projects - South Africa